Analysis of Substantial Criminal Law Studies - Sandi Situmorang (Enigma in Law, 2023)
Substantial criminal law analysis is a major and detailed way to examine, comprehend, and enhance significant parts of criminal law. The objective of this analysis is to guarantee that criminal law upholds justice and safeguards the human rights of individuals, encompassing the right to a fair trial, the prohibition of torture, and protection against inhumane treatment. By doing a comprehensive review of criminal legislation, one can pinpoint vulnerabilities, such as ambiguous definitions of criminal crimes and the application of unsuitable penalties. The relevance of criminal law should consistently align with societal shifts, communal principles, and advancements in scientific knowledge. A thorough examination of criminal law is crucial to ensuring that it adjusts to these advancements. The results of this study can be used as a guide to make smarter decisions about criminal law. This could mean changing how crimes are dealt with or making new laws. By analyzing data, judging deterrence, and coming up with better ways to stop crime, analysis helps figure out how well criminal law works at stopping people from breaking the law. Safeguarding the rights of those who are under suspicion or facing charges is of utmost importance. A thorough examination of criminal law assures that the criminal legal process includes safeguards for impartial investigation, prosecution, and incarceration.